Осадження металічних плівок на мікрочастинки у пастці ВЧ магнетронного розряду - Pal, A.F.; Rudavets, A.G.; Ryabinkin, A.N.; Serov, A.O. (Publishing house "Academperiodika", 2022)
The technique for a metal film deposition on spherical microparticles in an RF plasma trap is presented. Both the particle confinement and the electrode sputtering are performed by a single RF magnetron discharge. The samples of a coated spheres are obtained and examined. The technique allows confining the particles near to the sputtered region close to the border zone of ballistic bombardment by sputtered atoms.